Evaluation of dry eyes after eyelid surgery - Ali, Hala Adnan; Jalloul, Kahtan; Darwish, Taym (Journal of medical and pharmaceutical sciences, 2022)
Objective: Investigating the change in tear and dry eye indicators before and after blepharoplasty by means of the ocular surface disease index questionnaire (OSDI), tear film break-up time test (TFBUT), and monitoring the change in the amount of tear secretion after the operation. Using the Schirmer test.Effect of a conservative surgical technique on the orbicularis ocular muscle, its innervation and its association with postoperative dry eye.Methods: 30 patients (two males and twenty-eight females) who attended the ophthalmological clinic at Tishreen University Hospital in Lattakia/ Syria participated in this cross-sectional study during the time period from March 2020 to April 2021, after taking their written consent to conduct the research,. Patients' information was collected including gender and age. The tear film break-up time was also measured before surgery and the Schirmer test was performed for all patients. We asked patients to evaluate the degree of dryness they have in each eye using Ocular surface disease index questionnaire (OSDI), the questionnare was repeated the,at three time points, one week, 4 weeks and 24 weeks after the operation.All patients underwent upper blepharoplasty using the pinch technique.Results The patients' age ranged between 31-66 years and the mean age was 49.5 years, the mean OSDI value before surgery was (6.8 ± 4.5) with mild postoperative increase without statistically significance differences for P values.Also, we did not find a statistically significance change in the mean values of the tear film break up time test and the Schirmer test before and after the operation.There were two patients whom experienced mild dryness using OSDI with change of eye condition to moderate dryness after surgery.Conclusion: Evaluating the patient and investigating the presence of dry eyes before eyelid surgery avoids the occurrence or exacerbation of dryness after surgery, and surgery with preserving the orbicularis muscle reduces the possibility of dry eye syndrome after surgery.
Keywords: Evaluation; upper blepharoplasty; Dry eye; Schirmer test; tear film break-up time